INOVASI ASESMEN PEMBELAJARAN PENDIDIKAN ISLAM BERBASIS TEKNOLOGI UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS - Sevi Lestari; Nabila Putri Ramadhani; Ahmad Rizky Maulana (Jurnal Dinamika Pendidikan Islam, 2026)
The low level of Higher Order Thinking Skills (HOTS) among students in Islamic education learning is a pressing problem that requires innovative solutions. This study aims to analyze the effectiveness of technology-based assessment innovations in improving students' HOTS in Islamic education subjects. A quasi-experimental research design with pre-test and post-test control group was employed involving 240 students at eight madrasah aliyah in East Java. Results show that the group receiving technology-based assessment experienced a significant increase in HOTS scores with an N-Gain value of 0.67 (medium-high category), far surpassing the control group with N-Gain of 0.28. The most improved HOTS dimensions were analytical ability and critical evaluation of Islamic texts. The conclusion confirms that technology-based assessment is proven effective in improving HOTS and can be recommended as an innovative assessment model in Islamic education.